2017
DOI: 10.3892/etm.2017.4239
|View full text |Cite
|
Sign up to set email alerts
|

Roscovitine protects murine Leydig cells from lipopolysaccharide-induced inflammation

Abstract: Roscovitine is a cyclin-dependent kinase inhibitor, which has been previously investigated for its anticancer effects. It has also been confirmed that roscovitine can downregulate the expression of myeloid cell leukemia-1 protein to inhibit inflammation. In the present study, roscovitine was used to treat inflammation in lipopolysaccharide (LPS)-induced model mice. At the cellular level, Leydig cells isolated from mouse testis were assessed for inflammatory factors. It was revealed that roscovitine successfull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…LPS triggers the TLR signaling pathway through MyD88 adaptor molecules, resulting in the activation of the NF-κB and MAPK (p38 and ERK) pathways and infected germ cells ( Akira & Takeda, 2004 ; Beutler, 2004 ; Bhushan et al, 2015 ). Several transcription factors and molecules that protect germ cells from inflammatory responses have also been reported ( Li et al, 2013 ; Pan et al, 2016 ; Xie et al, 2017 ; Zhou et al, 2016 ). These results suggest the importance of gene therapy in the anti-inflammatory effects of germ cells.…”
Section: Discussionmentioning
confidence: 99%
“…LPS triggers the TLR signaling pathway through MyD88 adaptor molecules, resulting in the activation of the NF-κB and MAPK (p38 and ERK) pathways and infected germ cells ( Akira & Takeda, 2004 ; Beutler, 2004 ; Bhushan et al, 2015 ). Several transcription factors and molecules that protect germ cells from inflammatory responses have also been reported ( Li et al, 2013 ; Pan et al, 2016 ; Xie et al, 2017 ; Zhou et al, 2016 ). These results suggest the importance of gene therapy in the anti-inflammatory effects of germ cells.…”
Section: Discussionmentioning
confidence: 99%
“…Testosterone and its synthesis enzymes, CYP11A1 and 3β-HSD, were also decreased. CYP11A1 catalyzes the production of pregnenolone from cholesterol, while 3β-HSD is a critical enzyme involved in the conversion of pregnenolone to dihydrotestosterone and a marker highly-expressed in Leydig cells [38,39]. A low testosterone concentration is also considered a key effector of erectile dysfunction [40].…”
Section: Discussionmentioning
confidence: 99%
“…LPS has been widely used to generate animal models of inflammation to study the effect of inflammation in vivo . Injection of LPS produces an inflammatory response and inhibits testicular steroid production and subsequent spermatogenesis, and may also damage the blood-testis barrier, thereby decreasing fertility (19). In a previous study, C57 mice were intraperitoneally injected with LPS to induce an inflammatory response, in order to observe the histopathological changes in the cells (19).…”
Section: Discussionmentioning
confidence: 99%
“…Injection of LPS produces an inflammatory response and inhibits testicular steroid production and subsequent spermatogenesis, and may also damage the blood-testis barrier, thereby decreasing fertility (19). In a previous study, C57 mice were intraperitoneally injected with LPS to induce an inflammatory response, in order to observe the histopathological changes in the cells (19). In the present study, the serum testosterone levels decreased following LPS treatment, which indicated that inflammation damaged the normal functions of the Leydig cells.…”
Section: Discussionmentioning
confidence: 99%